Analysis of the Needs for Developing the Tazkiyatun Nafs Learning Model, Spiritual Growth Based in High School - Akbar, Muhammad; Asra, Muhammad; Rival, Muhammad; Hidayah, Miqdad; Ilham, Muhammad Arifin; Ishak, Ishak (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
This study is motivated by the challenges of character education in the Society 5.0 era, where rapid digital development significantly influences students’ behavior, discipline, and spirituality. Conventional character education, which emphasizes cognitive aspects, is considered insufficient; therefore, a model that incorporates spiritual dimensions is urgently needed. The concept of Tazkiyatun Nafs (self-purification) combined with the Spiritual Growth Framework (SGF) is deemed relevant to strengthen self-awareness, self-control, and moral values among secondary school students. This research aims to analyze the needs for developing a learning model based on Tazkiyatun Nafs within the SGF framework for senior high schools. The study employed a Research and Development (R&D) approach with a needs assessment as the initial stage. Data were collected through questionnaires (38 teachers), in-depth interviews, focus group discussions (24 teachers from 10 schools), and document analysis, and were analyzed using descriptive statistics and thematic analysis. The findings revealed that the integration of spiritual values into classroom learning remains partial and ceremonial. A total of 89% of teachers emphasized the need for a model that enhances students’ self-awareness, 95% highlighted the urgency of strengthening spiritual values, and 94% supported the development of a Tazkiyatun Nafs-based learning model. Teachers also recommended the preparation of practical modules and training to ensure effective implementation. This study concludes that integrating Tazkiyatun Nafs with SGF has strong potential as an innovative strategy for strengthening students’ character education in secondary schools.